EVALUATION OF RISK FACTORS OF COCCYDYNIA IN MIDDLE- AGED FEMALES - Shruti kumbhar,; Dr. G. Varadharajulu, (The Bioscan, 2025)
Introduction Coccydynia in middle age females has been increased in recent years. Coccydynia is a pain at the tailbone. This pain occurs due to many reasons like obesity, post-partum period, pregnancy, trauma, long sitting. The aim of this study was to evaluate the risk factors of coccydynia in middle age females. Method This was a ‘conventional sampling method’ that consisted of 100 participants and they were selected on the basis of inclusion and exclusion criteria. The data that was collected which includes demographic data and questionnaire. Questionnaire was given to all participants and collect the data. Result Based on statistical analysis it was found that there are many risk factors of coccydynia in middle age females but the postpartum period of female has more risk of developing coccyx pain 40% females has chance to develop coccyx pain due to postpartum period. obesity, long sitting professions, trauma are the other risk factors for the condition. Conclusion The study concluded that postpartum factors are the leading cause of coccydynia in middle-aged females, followed by lifestyle-related factors like long sitting and obesity. postnatal care, ergonomics, weight management, and trauma prevention is essential for effective evaluation and management of coccydynia in this population.